Therapeutics in paediatric genetic diseases: current and future landscape - Ai Ling Koh; Saumya Shekhar Jamuar (Singapore Medical Journal)
There are more than 7,000 paediatric genetic diseases (PGDs) but less than 5% have treatment options. Treatment strategies targeting different levels of the biological process of the disease have led to optimal health outcomes in a subset of patients with PGDs, where treatment is available. In the past 3 decades, there has been rapid advancement in the development of novel therapies, including gene therapy, for many PGDs. The therapeutic success of treatment relies heavily on knowledge of the genetic basis and the disease mechanism. Specifically, gene therapy has been shown to be effective in various clinical trials, and indeed, these trials have led to regulatory approvals, paving the way for gene therapies for other types of PGDs. In this review, we provide an overview of the treatment strategies and focus on some of the recent advancements in therapeutics for PGDs.